(untitled) (Indonesian Journal of Civil Engineering Study, 2024)
In this research regarding construction waste, the focus is on the study of waste management in the construction of the Nurul Huda Integrated Roudlatul Ulum Building project, Kudus Regency, which is being carried out in the 2023–2024 period. This self assessment aims to assess the effectiveness of building construction waste management and identify best practices and obstacles faced in their implementation. The methods used include surveys, interviews and direct observation at construction project sites in various regions. The assessment results show that the majority of projects have implemented waste reduction strategies, such as material recycling and the use of environmentally friendly building materials. However, there are still significant barriers to limiting waste at source and a lack of worker awareness and training regarding the importance of effective waste management. This research recommends improving training programs for workers, implementing more efficient waste management technology, and enforcing stricter regulations to ensure sustainable waste management. In the Nurul Huda Integrated Roudlatul Ulum Building Construction Project, Kudus Regency, the calculation of the performance assessment percentage was carried out by comparing the points achieved with the standards that became the reference points. The results show that 4 of the 7 points required to assess project performance if displayed becomes 57%. Thus, it is hoped that this research can contribute to the creation of a cleaner and environmentally friendly construction environment.